2000
DOI: 10.1038/35003550
|View full text |Cite
|
Sign up to set email alerts
|

Stable sulphate clusters as a source of new atmospheric particles

Abstract: The formation of new atmospheric particles with diameters of 3-10 nm has been observed at a variety of altitudes and locations. Such aerosol particles have the potential to grow into cloud condensation nuclei, thus affecting cloud formation as well as the global radiation budget. In some cases, the observed formation rates of new particles have been adequately explained by binary nucleation, involving water and sulphuric acid, but in certain locations--particularly those within the marine boundary layer and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
424
1
11

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 616 publications
(460 citation statements)
references
References 33 publications
24
424
1
11
Order By: Relevance
“…[13] It has been suggested that 1 nm is the size of a thermodynamically stable clusters, which under certain conditions grow to detectable sizes [Kulmala et al, 2000]. For this reason, the approximate starting time of formation of 1-nm particles was calculated.…”
Section: Particle Formation Rate and Growth Ratementioning
confidence: 99%
“…[13] It has been suggested that 1 nm is the size of a thermodynamically stable clusters, which under certain conditions grow to detectable sizes [Kulmala et al, 2000]. For this reason, the approximate starting time of formation of 1-nm particles was calculated.…”
Section: Particle Formation Rate and Growth Ratementioning
confidence: 99%
“…For instance, the number concentrations of atmospheric particles affects the microphysics of clouds, which may affect their rainfall, lifetime and optical properties and in turn, global climate (Penner et al, 2001;Twomey, 1977). In addition to mechanical and combustion processes, new particles can be created from the nucleation of gas phase species (Kulmala et al, 2000;Kulmala, 2003). These events have been observed in a variety of environments worldwide and may be a significant factor in the repopulation of particle numbers lost through deposition.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that in this particular environment, the biogenic VOCs and their oxidation products are responsible for the growth of the particles, although the initial formation is thought to happen though the nucleation of sulphuric acid with water and/or ammonia (Kulmala et al, 2000). For a detailed study into the initial nucleation and early stages of growth during this study, the reader is directed to Kulmala et al (2004a).…”
Section: Introductionmentioning
confidence: 99%
“…While conditions necessary for homogeneous nucleation do occur in the atmosphere, observations suggest that in some cases, new particles form more readily than models can predict for the homogeneous nucleation of sulfuric acid and water alone [Weber et al, 1995[Weber et al, , 1997. Thus other species, including ammonia and organic vapors, may participate in nucleation of new particles in some parts of the atmosphere [e.g., Ball et al, 1999;Kulmala et al, 2000].…”
Section: Introductionmentioning
confidence: 99%